2018
DOI: 10.1186/s12960-018-0302-z
|View full text |Cite
|
Sign up to set email alerts
|

Advancing the science behind human resources for health: highlights from the Health Policy and Systems Research Reader on Human Resources for Health

Abstract: Health workers are central to people-centred health systems, resilient economies and sustainable development. Given the rising importance of the health workforce, changing human resource for health (HRH) policy and practice and recent health policy and systems research (HPSR) advances, it is critical to reassess and reinvigorate the science behind HRH as part of health systems strengthening and social development more broadly. Building on the recently published Health Policy and Systems Research Reader on Huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 57 publications
(17 reference statements)
0
28
0
Order By: Relevance
“…Our final objective is to explore the social context of hygiene examining, for example, the normative status of handwashing and the influence of managers and other staff members. As advocated by George et al (2018) , we aim to go beyond seeing health workers as faceless numbers of units of health producers but instead recognising the importance of “their identities and motivations, daily routines and negotiations, and training and working environments”.…”
Section: Introductionmentioning
confidence: 99%
“…Our final objective is to explore the social context of hygiene examining, for example, the normative status of handwashing and the influence of managers and other staff members. As advocated by George et al (2018) , we aim to go beyond seeing health workers as faceless numbers of units of health producers but instead recognising the importance of “their identities and motivations, daily routines and negotiations, and training and working environments”.…”
Section: Introductionmentioning
confidence: 99%
“…The present study has demonstrated the usefulness of a trans-sectoral governance approach, which connects different policy sectors following a ‘whole of government’ perspective. 5 , 6 , 19 To our knowledge, trans-sectoral governance theories have not been applied systematically to the governance of LTC migrant carers and no comparative data exist. Our novel framework was able to draw a more comprehensive picture and to highlight the political dimensions 33 of the LTC migrant workforce in times of the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research and policy development on health human resources has also zoomed in on gender issues, in addition to other pressing topics such as the informal health care economy, dual practice (George, Campbell, & Ghaffar, 2018), migration (S. E. Johnson, Green, & Maben, 2014), and capacity building (Ridge, Klar, Stimpfel, & Squires, 2018). For instance, a recent World Health Organization report, endorsed new approaches to research and policy-making, with emphasis on structural, high-level factors (George, Scott, & Govender, 2017).…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%